Professional growth activities of selected public general secondary school teachers in the Division of Tarlac - Cala, Agripina B. 1910- (s.n.], 1969)
This study identified the professional growth activities of selected public secondary school teachers in the division of Tarlac. It was concluded that teachers' participation in professional growth activities is limited. Teachers, when grouped according to sex, civil status and subjects taught, vary lightly with regard to their extent of participation in professional growth activities. The major reason of teachers for participating in professional activities is to keep abreast with new approaches or modern methods of teaching. However, family responsibilities are found to be the major reason of teachers for not taking maximum advantage of the professional activities.